Mortalidade e comportamento de Aedes aegypti (Diptera: Culicidae) resistente a piretróides exposto ao óleo essencial de Aristolochia trilobata L. (Piperales: Aristolochiaceae) - Silva, Indira Morgana de Araújo (2017)
The Aedes aegypti is a vector of severe arboviruses such as dengue, february yellow, Zika and chikungunya, and other examples of resistance to pyrethroids have been identified in vector populations in several countries. In this work, we aim to analyze the effects of lethal and subtleties of the essential oil of Aristolochia trilobata and its major compounds on A. aegypti. The essential oil of A. trilobata was obtained by hydrodistillation in Clevenger apparatus and chemically analyzed by gas chromatography coupled to mass spectrometry and a flame ionization detector (GC / MS / DIC). They populations of A. aegypti susceptible PPCampos and resistant to pyrethroids Oiapoque were used. The bioassays were developed with larvae and adults to obtain concentrations/doses and lethal times, and only with larvae to evaluate the swimming behavior of these individuals. Twenty-five compounds were identified and quantified in the essential oil of A. trilobata, which represented 98.72% of the total composition. Among the bio-insecticides, the most toxic compound was limonene, for larvae, and the essential oil of A. trilobata, for adults, of the susceptible population. However, as larvae and adults of the resistant population showed approximately 100% mortality when treated with the ρ-cymene compound. This compound also caused a reduction in the survival of individuals in the resistant population, with a lethal time of 9.54 h and 0.08 h to kill 50% of larvae and adult females, respectively. The treatments modified the larval swimming behavior of the both populations and, in general, reduced their rates of displacement and velocity, as well caused greater disorientation of swimming. Thus, our results show possible alternatives to control larval and adult of A. aegytpi, including resistant to pyrethroids, and clarify the effects of insecticides on the behavior of larvae of this mosquito and its possible consequences on fitness of natural populations.